Pengembangan Media Infografis Interaktif (MIFOR) pada Materi Permasalahan Lingkungan yang Mengancam Kehidupan Siswa Kelas V Sekolah Dasar - Salsabila, Nabila Anastasia; Sukriadi; Hidayat, Taufik; Iksam (Mataram University, 2026)
The main problem in science and social studies (IPAS) learning at the elementary school level is students’ low understanding of environmental issues that threaten life. This problem is caused by the limited use of interactive and visual learning media, which leads students to become passive during the learning process. This study aims to develop an Interactive Infographic Media (MIFOR) on environmental issues that threaten life for fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research instruments included validation sheets from material experts, media experts, and language experts; student response questionnaires in small-group and large-group trials; and a teacher response questionnaire. The results showed that the MIFOR media obtained material expert validation percentages of 85.71% and 88.57%, media expert validation of 86.31% and 91.57%, and language expert validation of 100%, all categorized as very valid. The practicality of the media reached 87.04% in the small-group trial and 85.61% in the large-group trial, categorized as highly feasible. Teacher responses indicated that the MIFOR media is easy to use and appropriate for IPAS learning materials. Therefore, the MIFOR media is considered valid and practical for use in elementary school IPAS learning.